AZURE INTEGRATION GUIDE FOR BUSINESS master effective architecture strategies for business innovation - Garverick, Joshua; Lee, Jack; Qin, Mélony; Williams, Trevoir (Packt Publishing Ltd., 2023)
Leverage the cloud to optimize costs, improve security, and seamlessly scale your business operations Key Features Achieve your operational goals with Azure infrastructure Optimize costs with serverless event-driven solutions through Azure cloud patterns Boost productivity with Azure architecture's flexibility and scalability Purchase of the print or Kindle book includes a free PDF eBook Book Description Azure Integration Guide for Business is essential for decision makers planning to transform their business with Microsoft Azure. The Microsoft Azure cloud platform can improve the availability, scalability, and cost-efficiency of any business. The guidance in this book will help decision makers gain valuable insights into proactively managing their applications and infrastructure. You'll learn to apply best practices in Azure Virtual Network and Azure Storage design, ensuring an efficient and secure cloud infrastructure. You'll also discover how to automate Azure through Infrastructure as Code (IaC) and leverage various Azure services to support OLTP applications. Next, you'll explore how to implement Azure offerings for event-driven architectural solutions and serverless applications. Additionally, you'll gain in-depth knowledge on how to develop an automated, secure, and scalable solutions. Core elements of the Azure ecosystem will be discussed in the final chapters of the book, such as big data solutions, cost governance, and best practices to help you optimize your business. By the end of this book, you'll understand what a well-architected Azure solution looks like and how to lead your organization toward a tailored Azure solution that meets your business needs. What you will learn Optimize the performance and costs with Azure Select an effective, scalable, and flexible solution that aligns with your needs Harness the power of containers to drive your application development and deployment Create big data solutions with the best Azure tools, platforms, and resources Explore the benefits of automation for enhanced productivity Improve the availability and effectiveness of monitoring with Azure Who this book is for This book is for business decision makers looking to benefit from the flexibility, scalability, and optimized costs offered by Microsoft Azure to scale their businesses. Basic knowledge of Azure is recommended to get the most out of this book.